Crucial Interventions : an Illustrated Treatise on the Principles and Practice of Nineteenth Century Surgery. - Barnett, Richard (Thames & Hudson, Ltd., 2015)
The nineteenth century saw a complete transformation of the practice and reputation of surgery. Crucial Interventions follows its increasingly optimistic evolution, drawing from the very best examples of rare surgical textbooks with a focus on the extraordinary visual materials of the mid-nineteenth century. Unnerving and graphic, yet beautifully rendered, these fascinating illustrations include step-by-step surgical techniques paired with medical instruments and painted depictions of operations in progress. Arranged for the layman from head to toe, and accompanied by an authoritative, eloq.